AKTUALISASI MANAJEMEN PENINGKATAN MUTU BERBASIS MADRASAH - M. Sahibuddin M. Sahibuddin (STAI Ma'had Aly Al-Hikam Malang, 2015)
Execution conception of Islamic education marked with an institute, madrasah used to face several problems which relate to how education quality reached and fostered. It can be said that problems emerge in unexpected conditions such as poor of curriculum plan, inappropriate building management, environmental work that is not conducive, the problem of management that procedure and system are not in accordance, time learning allocation, and human resources, represent the unqualified education. Here, quality improvement management is viewed as a must. This article initiates in how problems solved and intentionally describes only how madrasah based quality improvement management is actualized through idiographic approach with an analyst of SWOT.